Intimate partner violence among lesbian, bisexual, and queer women students on campuses in South Africa: a qualitative study exploring context, drivers, and impacts - Pinky Mahlangu; Carrie Brooke-Sumner; Yandisa Sikweyiya; Kristin Dunkle; Ntlotleng Mabena; Rachel Jewkes; Sinegugu Duma; Nelisiwe Khuzwayo; Elizabeth Dartnall; Managa Pillay; Mercilene Tanyaradzwa Machisa (BMC Global and Public Health)
Abstract Background Intimate partner violence (IPV) is a global public health problem, associated with negative physical and mental health impacts. Research on IPV has mainly focused on heterosexual relationships with limited focus on same-sex relationships. This paper reports the findings of a qualitative study which explored experiences, context, drivers, and impact of IPV in same-sex relationships of students who identify as lesbian, bisexual, and queer (LBQ) women at three campuses in a university in South Africa. Methods We collected data through focus group discussions (FGDs) with 56 students who self-identified as LBQ women. Participants were Black African, between 18 and 30 years of age, enrolled in courses for at least 1 year, and volunteered to participate in group discussions. Data were analyzed inductively using a thematic analysis approach. We drew from the post-structural feminist theory to understand the relationship dynamics in same sex relationships of LBQ women. Results Three themes were developed through the analysis of data. The first theme is on the nature and forms of violence experienced by LBQ women—where women described bidirectional partner violence, including physical, sexual, and emotional IPV, and controlling behaviors in their relationships; and discrimination and disregard for bisexual women. Theme two highlighted the drivers and context of violence experience and enactment in intimate relationships which included multiple factors: past traumas, previous experience of violence, poor communication and poor conflict resolution skills, and heteronormativity and gender norms. IPV occurred when gender roles and expectations were not met, and when contesting for power and dominance in relationships. The last theme elaborates on the mental health impacts of IPV among LBQ women which included depression, anger, self-hate, and negatively impacted self-esteem. Furthermore, participants spoke of their mental health contributing to IPV perpetration and negatively affecting their academic outcomes. Conclusions Our findings suggest the need for IPV interventions that address both victimization and perpetration, given the occurrence of bidirectional violence. Such interventions should focus on building healthy and non-violent relationships and on promoting mental health of LBQ women students in same-sex relationships. Interventions should be co-developed with LBQ women on campuses for greater relevance and impact.